THE RELATIONSHIP OF KNOWLEDGE AND ATTITUDE OF ELDERLY TO HYPERTENSION INCIDENCE IN TAPIAN DOLOK HEALTH CENTER TAPIAN DOLOK DISTRICT SIMALUNGUN DISTRICT PERIOD - Wilson Samosir; Yulia Delfahedah; Mustaruddin (Universitas Efarina, 2021)
Hypertension in the elderly is mostly isolated systolic hypertension (HST), increased systolic pressure causes a greater likelihood of stroke and myocardial infarction even though the diastolic pressure is within normal limits (isolated systolic hypertension). Isolated systolic hypertension is the most common form of hypertension in the elderly. In one study, hypertension occupied 87% of cases in people aged 50 to 59 years. According to the World Health Organization, the elderly are grouped into: middle age, which is the age group of 45 -59 years. Elderly (Elderly): between 60-74 years, Old (Old): between 75-90 years, and very old (Very Old) over 90 years, the research method used is